(untitled) (Journal of the College of Basic Education, 2022)
Over three quarter of the world’s population is using herbal medicines with an increasing trend globally. the aim of this study was investigation of antibacterial activity of dried black lemon extract that have been extracted with 96% ethanol alone and in combination with some antibiotics (Ampiciline (AM(10 mcg)), Gentamycine (CN(10 mcg)) , Amoxiline (AX(25mcg)) , Erythromycine (E(15 mcg)) and Tetracycline (TE(30)) against local bacterial isolates Escherichia coli, Staphylococcus aureus , Protius mirabilis, Serratia marcescens and Pseudomonas aeruginosa . The results have shown a good antibacterial activity of the dried black lemon extract against all of the selected bacteria except Protius mirabilis .this extract helped in increasing the antibacterial activity of some antibiotics and decrease or not affect on other antibiotics when they tested on bacteria. The results of this study showed that ethanolic extracts of dried black lemon can be introduced as an alternative to chemical antimicrobial drugs, wider investigation is required.